Addressing frailty in patients with breast cancer: A review of the literature. Issue 1 (January 2020) - Jauhari, Yasmin; Gannon, Melissa Ruth; Dodwell, David; Horgan, Kieran; Tsang, Carmen; Clements, Karen; Medina, Jibby; Tang, Sarah; Pettengell, Ruth; Cromwell, David Alan
Abstract: Various studies have documented variation in the management of older patients with breast cancer, and some of this variation stems from different approaches to balancing the expected benefit of different treatments, with the ability of patients to tolerate them. Frailty is an emerging concept that can help to make clinical decisions for older patients more consistent, not least by providing a measure of 'biological' ageing. This would reduce reliance on 'chronological' age, which is not a reliable guide for decisions on the appropriate breast cancer care for older patients. This article examines the potential of frailty assessment to inform on breast cancer treatments. Overall, the current evidence highlights various benefits from implementing comprehensive geriatric assessment and screening for frailty in breast cancer patients. This includes a role in supporting the selection of appropriate therapies and improving physical fitness prior to treatment. However, there are challenges in implementing routine frailty assessments in a breast cancer service. Studies have used a diverse array of frailty assessment instruments, which hampers the generalisability of research findings. Consequently, a number of issues need to be addressed to clearly establish the optimal timing of frailty assessment and the role of geriatric medicine specialists in the breast cancer care pathway.